WNT/β-Catenin Signaling Is Required for Integration of CD24+ Renal Progenitor Cells into Glycerol-Damaged Adult Renal Tubules - Zhao Zhang; Diana M. Iglesias; Rachel Corsini; LeeLee Chu; Paul Goodyer (Stem Cells International)
During development, nephron progenitor cells (NPC) are induced to differentiate by WNT9b signals from the ureteric bud. Although nephrogenesis ends in the perinatal period, acute kidney injury (AKI) elicits repopulation of damaged nephrons. Interestingly, embryonic NPC infused into adult mice with AKI are incorporated into regenerating tubules. Since WNT/β-catenin signaling is crucial for primary nephrogenesis, we reasoned that it might also be needed for the endogenous repair mechanism and for integration of exogenous NPC. When we examined glycerol-induced AKI in adult mice bearing a β-catenin/TCF reporter transgene, endogenous tubular cells reexpressed the NPC marker, CD24, and showed widespread β-catenin/TCF signaling. We isolated CD24+ cells from E15 kidneys of mice with the canonical WNT signaling reporter. 40% of cells responded to WNT3a in vitro and when infused into glycerol-injured adult, the cells exhibited β-catenin/TCF reporter activity when integrated into damaged tubules. When embryonic CD24+ cells were treated with a β-catenin/TCF pathway inhibitor (IWR-1) prior to infusion into glycerol-injured mice, tubular integration of cells was sharply reduced. Thus, the endogenous canonical β-catenin/TCF pathway is reactivated during recovery from AKI and is required for integration of exogenous embryonic renal progenitor cells into damaged tubules. These events appear to recapitulate the WNT-dependent inductive process which drives primary nephrogenesis.